Dissolvable polyvinyl-alcohol film, a time-barrier to modulate sample flow in a 3d-printed holder for capillary flow paper diagnostics - Yitian, Alicia Lu (2019)
Integrating a dissolvable membrane into a sensor allows the control of sample flow, location and duration in critical areas. These time-barrier films stop the flow of samples until the membrane has dissolved, thus, for example, allowing increased exposure time between immunoreagents for the formation of greater numbers of immuno-complexes, ensuring higher sensitivity, reactivity, and helping to reduce false-positive signals. In this study, dissolvable polyvinyl alcohol (PVA) films are used in a 3D-printed sensor holder, which enables film integration without the use of glue. PVA is a synthetic hydrophilic linear polymer, its solubility is dependent on its molecular weight and degree of hydrolysis. Three types of PVAs films were tested herein: (1) PVA 1-Mw: 30–70 K, 87–90% hydrolyzed; (2) PVA 2-Mw: 31–50 K, 98–99% hydrolyzed and (3) PVA 3-Mw: 89–98 K, >99% hydrolyzed. The films were exposed to water in (1) the novel 3D-printed holder and (2) directly immersed into a water droplet. After comparing the time taken to dissolve PVA 1–3 films, PVA 1 films of 5–20% (w/v) are found to be most suitable as time barrier films, due to their optimal dissolution times and physical properties for integration into the customized 3D-printed holder.